2019
DOI: 10.1038/s41598-019-56525-5
|View full text |Cite
|
Sign up to set email alerts
|

Database of adverse events associated with drugs and drug combinations

Abstract: Due to the aging world population and increasing trend in clinical practice to treat patients with multiple drugs, adverse events (AEs) are becoming a major challenge in drug discovery and public health. In particular, identifying AEs caused by drug combinations remains a challenging task. Clinical trials typically focus on individual drugs rather than drug combinations and animal models are unreliable. An added difficulty is the combinatorial explosion in the number of possible combinations that can be made u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…The overall incidence was 8.2% during the entire 49weeks. However, due to the increasing trend in clinical practice to treat elderly patients with multiple medications (Poleksic and Xie, 2019), it remains a challenge to identify if these adverse events were caused by EAHE consumption. Yet, reports on genotoxicity (Li et al, 2014a), acute toxicity (Li et al, 2018a), 28 days subchronic toxicity (Li et al, 2014b) 90 days subchronic toxicity (Lee et al, 2019) and teratotoxicity (Li et al, 2018a) have been conducted in animals and showed no adverse effects.…”
Section: Discussionmentioning
confidence: 99%
“…The overall incidence was 8.2% during the entire 49weeks. However, due to the increasing trend in clinical practice to treat elderly patients with multiple medications (Poleksic and Xie, 2019), it remains a challenge to identify if these adverse events were caused by EAHE consumption. Yet, reports on genotoxicity (Li et al, 2014a), acute toxicity (Li et al, 2018a), 28 days subchronic toxicity (Li et al, 2014b) 90 days subchronic toxicity (Lee et al, 2019) and teratotoxicity (Li et al, 2018a) have been conducted in animals and showed no adverse effects.…”
Section: Discussionmentioning
confidence: 99%
“…Drugs can be toxic or cause adverse events. Toxicity can be detected via ad-hoc in vitro ed in vivo experiments or it can be predicted via in silico models [Zhang et al, 2018],[Ganter et al, 2005],[Igarashi et al, 2015],[Alexander-Dann et al, 2018],[Poleksic and Xie, 2019]. Any of these techniques should be applied downstream to the use of DrugMerge for extra safety.…”
Section: Discussionmentioning
confidence: 99%
“…The scope of this project only covers the inclusion of ADRs resulting from DDIs reported in the TWOSIDES data table. Further improvements through enrichment of observed ADRs for drug pairs can be achieved by integrating the above with DrugBank's DDI (Wishart et al, 2018) , all drug-drug side effects reported in SIDER (Kuhn et al, 2016) and PAERS (Poleksic & Xie, 2019) .…”
Section: Discussionmentioning
confidence: 99%